Comparison of Open Sublay Mesh Repair and IPOM Technique for Ventral Hernia Repair - Niaz, Maryam Ishrat; Murtaza, Ghulam; Ahmad, Hafiz Naweed; Ahmad, Shafiq; Khalid, Annam; Akhtar, Naveed (Biological and Clinical Sciences Research Journal, 2025)
Ventral hernias, caused by a weakness in the abdominal wall muscles, are common in Pakistan and pose significant challenges to patient well-being. These hernias can manifest in various forms, including incisional, para-stromal, umbilical, epigastric, and Spigelian types, each with distinct surgical considerations. Both traditional open repair and minimally invasive techniques have been employed to manage these defects. This study aims to evaluate and compare the clinical outcomes of Open Sublay Mesh repair versus the laparoscopic intraperitoneal onlay mesh (IPOM) technique, focusing on key parameters such as hospital stay duration, postoperative pain, and infection rates. Methods: A Prospective Comparative study was conducted over nine months at the Department of Surgery, Nishtar Medical University, Multan. A total of 144 patients meeting the inclusion criteria were enrolled and randomly assigned to two groups: Group A (n = 72) underwent the conventional Open Sublay Mesh repair, and Group B (n = 72) received the Laparoscopic IPOM technique. Preoperative evaluation included demographic data and baseline clinical parameters. Postoperative outcomes were assessed at three intervals: on the first postoperative day, at 15 days, and one month. Pain was measured using standardized scoring systems, and infection was assessed based on clinical examination and laboratory results. Statistical analysis was performed using appropriate tests, with a significance level set at a P-value of less than 0.05. Results: The mean age was 39.43 years in Group A and 42.13 years in Group B, with no statistically significant difference in age (P = 0.61). However, the gender distribution differed significantly between the groups (P = 0.049), with a higher proportion of females. The mean hospital stay was substantially more extended in Group A (4.18 days) compared to Group B (2.32 days), with a p-value of 0.031. On the first postoperative day, 29.16% of patients in Group A reported pain, which decreased to 9.72% by one month. In contrast, Group B experienced pain in 22.22% of patients on day 1, with complete resolution by one month (P = 0.021). Infection rates were lower in the IPOM group, with 4% of patients exhibiting infection at 15 days and 1.38% at one month, compared to 8.33% and 2.77%, respectively, in the Open Sublay Mesh group (P = 0.012). Conclusion: The Laparoscopic IPOM technique demonstrated superior clinical outcomes, including shorter hospital stays, reduced postoperative pain, and lower infection rates, compared to the traditional Open Sublay Mesh repair. These findings suggest that IPOM may be a more favorable approach for managing ventral hernias, offering significant advantages over conventional open repair techniques.